2005
DOI: 10.1097/01.pcc.0000160596.31238.72
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of prognostic factors associated with outcome in pediatric severe sepsis: What is the role of steroids?*

Abstract: From this administrative database analysis, there is no evidence that steroids are associated with improved outcome in critically ill infants and children with sepsis. Although steroids may be given preferentially to more severely ill children, their use was associated with increased mortality. Clinicians should maintain equipoise on this topic pending prospective randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 9 publications
7
39
0
Order By: Relevance
“…Markovitz et al studied over 6,000 subjects using the Pediatric Health Information System administrative database and reported that corticosteroids were associated with increased mortality, although they were not able to account for illness severity [13]. Zimmerman et al analyzed the results of the largest interventional clinical trial in pediatric sepsis and found that corticosteroids were not associated with improved outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markovitz et al studied over 6,000 subjects using the Pediatric Health Information System administrative database and reported that corticosteroids were associated with increased mortality, although they were not able to account for illness severity [13]. Zimmerman et al analyzed the results of the largest interventional clinical trial in pediatric sepsis and found that corticosteroids were not associated with improved outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis of small trials showed no benefit attributable to corticosteroids [12]. In addition, two large retrospective observational studies did not show any survival benefit with corticosteroid use in children with septic shock [13], [14]. One of these studies normalized for illness severity and organ failure burden, but did not specifically conduct a risk-stratified analysis [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a larger survey, the PHIS database was analysed and use of steroids was associated with increased mortality. 55 Adrenal function was not assessed in this study. On the basis of these findings of lack of benefit, we suggest that it is both ethical and prudent to further study the role of hydrocortisone treatment in paediatric patients with relative adrenal insufficiency.…”
Section: Recommendationsmentioning
confidence: 97%
“…On day 4 post admission, low-dose intravenous methylprednisolone was started due to persistent hypoalbuminaemia, increased oxygen requirements and risk of septic shock 8. On day 6, the patient became tachycardiac and hypotensive and the blood results showed neutropaenia (WBC 3.25 × 10 3 ), thrombocytopaenia (82 × 10 3 ), anaemia (haemoglobin 8 g/dl) and coagulopathy (D-dimer elevated to 2055 ug/l, prothrombin time rose to 16 s and partial prothrombin time went up to 53 s).…”
Section: Case Presentationmentioning
confidence: 99%